A novel cover material improves cooling energy and fertigation efficiency for glasshouse eggplant production. (15th July 2022) - Lin, Terry; Goldsworthy, Mark; Chavan, Sachin; Liang, Weiguang; Maier, Chelsea; Ghannoum, Oula; Cazzonelli, Christopher I.; Tissue, David T.; Lan, Yi-Chen; Sethuvenkatraman, Subbu; Lin, Han; Jia, Baohua; et al.
Abstract: Glasshouses hold the potential to improve global food security, but high energy costs are an ongoing challenge in bringing them to the forefront of agriculture in warm climates. Here, the energy-saving potential of a 'Smart Glass' (SG), diffuse glass fitted with ULR-80 film which permits transmission of 85% of photosynthetically-active light and blocks heat-generating radiation, was characterised for a warm-climate glasshouse. Two consecutive 6-month trials of eggplant crops were grown in a high-tech glasshouse to compare SG to standard diffuse glass (control) in both cool and warm climate conditions. The SG reduced cooling energy use by 4.4% and fertigation demand by 29% in cooler months, and reduced cooling energy use by 4.4% and fertigation demand by 18% in warmer months. The SG did not significantly affect ventilation or heating energy use, but substantially reduced fruit yield. SG may be beneficial for reducing nutrient/water use alongside minor energy savings in commercial glasshouses. However, re-engineering the spectral characteristics of SG could improve eggplant fruit yield while maintaining reductions in energy, nutrient, and water use in the glasshouse. Highlights: A commercial 'Smart Glass' solar film produces minor reductions in energy-use for glasshouses in warm climates. The solar film reduces water-use by reducing crop transpiration and reducing light intensity. Cooling loads remain more dependent on convection and conduction than insolation through glass. Considerable reductions in eggplant yield result from light-limited photosynthesis.